Localization of Sphingolipid Enriched Plasma Membrane Regions and Long-Chain Base Composition during Mature-Fruit Abscission in Olive - Parra-Lobato, Maria C.; Paredes, Miguel A.; Labrador, Juana; Saucedo-García, Mariana; Gavilanes-Ruiz, Marina; Gomez-Jimenez, Maria C. (Frontiers in Plant Science, 2017)
Sphingolipids, found in membranes of eukaryotic cells, have been demonstrated to carry out functions in various processes in plant cells. However, the roles of these lipids in fruit abscission remain to be determined in plants. Biochemical and ﬂuorescence microscopy imaging approach has been adopted to investigate the accumulation and distribution of sphingolipids during mature-fruit abscission in olive (Olea europaea L. cv. Picual). Here, a lipid-content analysis in live protoplasts of the olive abscission zone (AZ) was made with fluorescent dyes and lipid analogues, particularly plasma membrane sphingolipid-enriched domains, and their dynamics were investigated in relation to the timing of mature-fruit abscission. In olive AZ cells, the measured proportion of both polar lipids and sphingolipids increased as well as endocytosis was stimulated during mature-fruit abscission. Likewise, mature-fruit abscission resulted in quantitative and qualitative changes in sphingolipid long-chain bases (LCB) in the olive AZ. The total LCB increase was due essentially to the increase of t18:1(8E) LCBs, suggesting that C-4 hydroxylation and Δ8 desaturation with a preference for (E)-isomer formation were quantitatively the most important sphingolipids in olive AZ during abscission. However, our results also showed a specific association between the dihydroxylated LCB sphinganine (d18:0) and the mature-fruit abscission. These results indicate a clear correlation between the sphingolipid composition and mature-fruit abscission. Moreover, measurements of endogenous sterol levels in the olive AZ revealed that it accumulated sitosterol and campesterol with a concomitant decrease in cycloartenol during abscission. In addition, underlying the distinct sterol composition of AZ during abscission, genes for key biosynthetic enzymes for sterol synthesis, for obtusifoliol 14α-demethylase (CYP51) and C-24 sterol methyltransferase2 (SMT2), were up-regulated during mature-fruit abscission, in parallel to the increase in sitosterol content. The differences found in AZ lipid content and the relationships established between LCB and sterol composition, offer new insights about sphingolipids and sterols in abscission.